Spatial patterns of invertebrate communities in spring and runoff-fed streams : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Ecology at Massey University, Palmerston North, New Zealand - Barquín Ortiz, José (Massey University, 2004)
Invertebrate spatial patterns were investigated in 36 and 12 spring and runoff-fed streams in New Zealand and in Northern Spain, respectively. Moss biomass and resource levels were more abundant in springbrooks than in runoff-fed streams. Invertebrate densities were greater in spring habitats, but invertebrate richness was higher and lower at more stable sites in New Zealand and Spain, respectively. These differences in invertebrate diversity may be related to the larger diversity of invertebrate predators in New Zealand springbrooks, and the lack of temperature mediated life history cues in the New Zealand invertebrate fauna. I carried out two experiments to look at the effect of local factors on the spatial distribution of invertebrate communities. The first experiment investigated the effect that algal biomass and habitat structure had on stream invertebrate communities. To do this I used artificial canopies to reduce algal growth and artificial substrates with different habitat complexities. Numbers of invertebrate taxa and individuals were both lower on bricks under the artificial canopies and on the simplest substrates. Algal productivity may enhance invertebrate richness by increasing the number of individuals in a given area, whereas habitat complexity may increase invertebrate richness by providing greater food and/or space resources. The second experiment examined the effects of primary productivity and physical disturbance on stream invertebrates by using artificial canopies and by kicking and raking patches of the stream bed (10 m2). We compared the effects of natural versus experimental disturbance on the benthic invertebrate fauna Invertebrate fauna in high productivity patches recovered quicker than in low productivity patches after both experimental and natural disturbance. The experimental disturbance reduced number of invertebrate taxa and individuals to a greater extent than the spate. Primary productivity limited the recovery of the invertebrate fauna after the disturbances. I also investigated temperature patterns in five runoff and seven spring-fed streams in the North and South Islands of New Zealand. The invertebrate fauna was sampled at 4 distances (0, 100, 500 and 1 km) from seven spring sources. Temperature variability was much larger for runoff-fed streams than for springs, and it increased with distance from the source. Flow, altitude, and the number and type (i.e., spring or runoff-fed) of tributaries joining the springbrook channel determined the degree of temperature variability downstream of the spring sources. Moving downstream, invertebrate communities progressively incorporated taxa with higher mobility and those more common to runoff-fed streams. Changes in substrate composition, stability and invertebrate drift are more likely explanations of the observed longitudinal patterns in the invertebrate communities than changes in temperature regimes.
Keywords: Freshwater invertebrates; Ecology; Stream ecology; New Zealand; Fields of Research::270000 Biological Sciences::270700 Ecology and Evolution::270701 Freshwater ecology